IDENTIFICATION OF OIL RESERVOIR MICROORGANISMS BY 16S rRNA - Karabalayeva, D.Y.; Abitay , A.N.; Batayeva , D.S.; Sadykova , D.A. (Eurasian Journal of Applied Biotechnology, 2022)
According to today's forecasts, global oil reserves may decrease over the next 50 years. Kazakhstan is one of the leading countries in the world in terms of oil resources. With modern methods, only half of the oil in the fields can be extracted. In this regard, the relevance is due to the growing interest in finding ways and means to increase oil recovery, especially to the constant use of microbiological methods. Oil is an important source of energy and chemical raw materials. Its reserves are limited and irreplaceable. The existing methods allow us to extract up to 40-60% of geological oil reserves in the development of oil fields. One of the most urgent tasks is to create the most effective methods to increase oil production in the developed fields. Microbiological methods used to increase oil production attract attention with their high efficiency and environmental safety, low capital intensity. In biotechnology, additional oil displacement occurs to a certain extent, these mechanisms provide both physical and chemical methods, but since the metabolites of microorganisms are formed directly in the plate openings, their impact efficiency is higher. It is impossible to master these methods without taking into account the microbiological and physico–chemical conditions in oil plates.